Oral Health of Parkinson’s Disease Patients: A Case-Control Study - Marjolein A. E. van Stiphout; Johan Marinus; Jacobus J. van Hilten; Frank Lobbezoo; Cees de Baat (Parkinson's Disease)
The aim of the study was to examine the oral health status of Parkinson’s disease (PD) patients, to compare their oral health status to that of a control group, and to relate it to the duration and severity of PD. Materials and Methods. 74 PD patients and 74 controls were interviewed and orally examined. Among PD patients, the duration and the Hoehn and Yahr stage (HY) of the disease were registered. Results. More PD patients than controls reported oral hygiene care support as well as chewing/biting problems, taste disturbance, tooth mobility, and xerostomia, whereas dentate patients had more teeth with carious lesions, tooth root remnants, and biofilm. Both longer duration and higher HY were associated with more chewing problems and, in dentates, more teeth with restorations. In dentates, longer duration of the disease was associated with higher number of mobile teeth. Higher HY was associated with more oral hygiene care support as well as biting problems and, in dentates, more teeth with carious lesions and tooth root remnants. Conclusions. Comparatively, PD patients had weakened oral health status and reduced oral hygiene care. Both duration and severity of the disease were associated with more oral health and hygiene care problems.